Rozwiąż równanie
a) 2(x-½)-x+3=3
b) 0=3-(2x+1)
c) 0=(x-1)-(3x-5)
d)(-½x+1)+3x/2 =3
e)3(1-x)-(1-2x)=9
f) 0,5(2-4x)=3-x
g)12y-(y+5)=10y-1
h)2(u-5)+15=3(u-4)+10
i)-3(y/3+1)-2=4(1-y)
j)2(3a-2)-6=4,5(2a-1)+½

Pilne na jutro !!!!!!!!!!!!!!!!!!!!!

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-09T15:10:03+01:00
A) 2(x-½)-x+3=3
2x-1-x+3=3
x=3-3+1
x=1

b) 0=3-(2x+1)
0=3-2x-1
2x=3-1
2x=2/:2
x=1


c) 0=(x-1)-(3x-5)
0=x-1-3x+5
3x-x=-1+5
2x=4/:2
x=2

d)(-½x+1)+3x/2 =3
-1/2x+1+3x/2=3/*2
-x+2+3x=6
2x=6-2
2x=4/:2
x=2

e)3(1-x)-(1-2x)=9
3-3x-x+2x=9
-3x+2x=9-3+1
-x=7/:(-1)
x=-7


f) 0,5(2-4x)=3-x
1-2x=3-x
-2x+x=3-1
-x=2/:(-1)
x=-2


g)12y-(y+5)=10y-1
12y-y-5=10y-1
12y-y-10y=5-1
y=4


h)2(u-5)+15=3(u-4)+10
2u-10+15=3u-12+10
2u-3u=10-15-12+10
-u=-7/:(-1)
u=7

i)-3(y/3+1)-2=4(1-y)
-3y/3-3-2=4-4y/*3
-3y-9-6=12-12y
-3y+12y=9+6+12
9y=27/:9
y=3


j)2(3a-2)-6=4,5(2a-1)+½
6a-4-6=8a-4,5+1/2
6a-8a=4+6-4,5+0,5
-2a=6/:(-2)
a= -3